Biodegradation and biotransformation of petroleum hydrocarbons: progress, prospects, and challenges - Felisardo, Raul José Alves; Gonçalves, Amanda de Azevedo (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2023)
Oil is considered the main source of energy, being essential for the realization of various industrial activities. However, it is detrimental to the environment, since in addition to the release of polluting gases during combustion, its exploitation involves risks of water contamination, through leaks. Petroleum hydrocarbon pollutants are part of the recalcitrant compounds and their elimination from the environment causes enormous ecological impacts. The restoration of these environments is not a trivial challenge, as natural degradation, without anthropogenic involvement, depends on the nature, composition, physical and chemical properties of these compounds. Thus, bioremediation appears as alternative in the biodegradation process through the addition of microorganisms, nutrients or other substances that cause and accelerate decontamination. The advantages of these methods involve efficiency and low cost, when compared to other technologies. This work gathers knowledge about the perspectives of application of bioremediation systems in the recovery of environments polluted by petroleum hydrocarbons, discussing progress, perspectives and challenges.